Initial biomechanical characteristics of elite shotgun shooting - Bourne, M.; Fowler, N.; Holmes, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Olympic shotgun is a technically complex sport, consisting of highly constrained movements that must be implemented in a precise manner to meet the performance goals of tracking and shooting moving targets. At the elite level, failure in a single trial can often be the difference between first and the lower placings. Understanding biomechanical variables within shotgun is important as a model of the biomechanical characteristics of shotgun shooting may expose pathways for technical optimisation. Previous research in shooting investigating balance and posture has used either the rifle or pistol disciplines. While some of the basic principles and methods of this research can be applied to shotgun, the varying constraints of the disciplines mean that to apply the findings directly from pistol or rifle to shotgun is questionable. The aim of this research was to determine the movement and balance characteristics of a single discipline of Olympic shotgun, forming an initial descriptive model of shotgun that could be compared and contrasted with future findings from the other disciplines. Methods A group of elite skeet shooters (n=6) undertook a series of ten shooting trials under a normal competition setting. Five trials were undertaken for each of two target release conditions, high tower and low tower. During each trial participants stood on a 60cm2 AMTI strain gauge force plate. For each trial 2D video data were acquired using two digital video cameras. Simultaneously, force data were collected for each trial from the force plate. Video data sets were synchronised offline then digitised using an 18 point full body model and 3D coordinates reconstructed via a DLT algorithm. Values of hip, shoulder and gun angle, interheel distance, base of support orientation and trunk lean were extracted and processed, as were centre of pressure (COP) motion characteristics, using both quantitative and qualitative methods. Results Across both the kinematic and kinetic variables, greater levels of consistency across trials were found at the intra-participant level than the inter-participant. Core patterns of both musculoskeletal and COP motion were found across all participants. Support base properties were constant within and between participants and the base of support were stationary during the execution of the skill. For all participants, the shoulders and hips showed tight locking between their rotations. While some individual motion was present for each, the majority of the rotational motion occurred from the locking between the two elements. The hips and lower limbs were, therefore, responsible for the majority of the rotation. Change in gun angle was comparable to the rotation of the hip-shoulder union, suggesting that gun rotation is driven by the rotation of hips rather than motion of the upper limbs in isolation (see table. 1). COP motion exhibited two distinct phases. The initial component related to the mounting phase of the skill shows characteristics pertaining to preparation for the maintenance of balance. The second, tracking phase shows characteristics that potentially minimise the possibility of balance disturbance. Discussion/Conclusion The results suggest elite skeet shooters use a general strategy within the task and environmental constraints to successfully complete the task. However, each individual manipulated themselves within the environment in a specific way to meet the task goal and exhibited intra-participant variance trial to trial. Technical support structures should focus on intra-individual analysis methods to support elite shooters in an optimal manner.